Nanofibras de poli(tereftalato de etileno) (PET) reciclável eletrofiadas e impregnadas com nanotubos de carbono para serem aplicadas na filtração de gases tóxicos - Medeiros, Gabriela Brunosi (2024)
The development of new materials in the manufacturing of more effective filtering media for the control of gaseous pollutants has attracted significant interest from industries in various sectors in recent years. This is due to the adverse effects of air pollution on human health, coupled with increasingly stringent environmental laws governing ultrafine particulate matter control. In an attempt to develop air filters with high collection efficiency for nanoparticles, the fabrication of membranes composed by nanofibers has gained prominence in both the scientific and industrial domains. Thus, the main objective of this study was the production of recyclable poly(ethylene terephthalate) (PET) nanofiber membranes impregnated with single-walled carbon nanotubes (SWCNTs) that exhibit high performance in filtering nanoparticles in gas streams, as well as adsorption of CO2 gas. For this purpose, a factorial design was employed, statistically analyzing process parameters such as concentration, injection flow rate, and applied voltage, with the average diameter as the response variable. Morphological, structural, and thermal characterizations of the developed nanofibers were conducted. As a result, poly(ethylene terephthalate) (PET) filters were obtained through the electrospinning technique with average diameters ranging from 300 to 600 nm. These filters demonstrated high performance in the filtration of fine particulate matter, with efficiencies of 95.7% and 99.8%, and pressure drops of 48.5 Pa and 223 Pa, respectively. Filters produced with SWCNTs showed no structural or thermal changes compared to PET-produced filters, while also proving effective in the removal of fine particulate matter. CO2 adsorption tests were conducted on the filtering media produced with SWCNTs. The filters produced through impregnation in both tested methodologies exhibited good CO2 adsorption capacity: 5.63 mg/g and 5.49 mg/g for surface impregnation and solution impregnation, respectively. Therefore, based on the obtained results, it can be stated that PET/SWCNT filters are promising for application for air and gas filtration systems, as they were efficient in removing fine particulate matter and adsorbing toxic gases such as CO2.